Cimarron Horse Show July 3, 1937 (Raton, NM Daily Range Print, 1937)
This is a program handed out for the Cimarron Horse Show on July 3, 1937.
Program printed on both sides
Mater List Item # 11
File location is in the New Mexico File Cabinets
Keywords: Springer, Ed -- President of Cimarron Polo Club; Mitchell, H. D; Smith, Don; Bridges, Ed; Saunders, Major; Fudge, Harry A; Kilbridge, John; Wilson, B. V; Cimarron Polo Club, Inc; Vallejo Polo Team; C.S. Polo Team; Horses; Horse Polo; Events; Programs; Awards; Cimarron Rodeo Grounds; Cimarron, New Mexico